2020
DOI: 10.1080/13621718.2020.1846936
|View full text |Cite
|
Sign up to set email alerts
|

Shielded metal arc welding of 9%Ni steel using matching ferritic filler metal

Abstract: Motivated by the tensile strength loss of 9%Ni steel arc welded joints made using Ni-based austenitic filler metals, the feasibility of maintaining the tensile strength using matching ferritic filler metal has been demonstrated. In comparison with shielded metal arc welded joint made using Ni-based austenitic electrode ENiCrMo-6, higher tensile strength comparable to that of the base metal was obtained using matching ferritic electrode. Besides, sufficient impact toughness energies with much lower mismatch wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 16 publications
(19 reference statements)
1
5
0
Order By: Relevance
“…As a result, 200 °C was considered to be the optimum preheating temperature since it also has a positive effect on the manufacturing cost. It is also important to highlight that PWHT resulted in a hardness profile close to that of the optimum preheated joint and similar to that of previously published research on SMAW with 9%Ni steel [ 28 ]. This is due to a tempered martensitic structure with a more stable retained austenite.…”
Section: Resultssupporting
confidence: 83%
See 2 more Smart Citations
“…As a result, 200 °C was considered to be the optimum preheating temperature since it also has a positive effect on the manufacturing cost. It is also important to highlight that PWHT resulted in a hardness profile close to that of the optimum preheated joint and similar to that of previously published research on SMAW with 9%Ni steel [ 28 ]. This is due to a tempered martensitic structure with a more stable retained austenite.…”
Section: Resultssupporting
confidence: 83%
“…PWHT was performed at a temperature of 580 °C (1076 °F). The holding time was 20 min [ 28 ]. The cooling down of samples was conducted in an ambient atmosphere.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Improvements in properties and the study of crack behavior of dynamically loaded materials and weld joints in a variety of steel types has attracted the attention of numerous authors [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 ]. In previous research [ 16 ] on martensitic steel P91, it was found that in the as-welded condition, the IC HAZ (intercritical HAZ) exhibited significantly higher impact toughness than the FG HAZ (fine-grained HAZ), while in the CG HAZ (coarse-grained HAZ), it was the lowest.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, major shipbuilders, who are responsible for the maintenance of most existing LNG tanker fleets, have started searching for inexpensive filler metals to meet their economic requirements. [14][15][16][17] Various alternatives have been studied to meet the rapidly increasing demand for cost-effective filler materials, and Fe-based alloys have emerged as the most efficient substitute for Ni-based alloys. In general, filler materials of Febased alloys form a ferrite phase in the WM and are therefore not suitable for use in welding 9% Ni steel.…”
mentioning
confidence: 99%